Nglangkahi Wedding Traditions in Lengkong Village, Bojong District, Tegal City Based on Urf and Sociology Study - Sulistiyowati, Anita (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Human behavior in choosing a life partner certainly has its own considerations. Sometimes considerations are not just material issues but also immaterial issues. In carrying out a wedding, there is a tradition that is still preserved and guarded by the community, even though this tradition is an unwritten law, it is certain that every region has living traditions that have been in effect for generations. This tradition must be obeyed by the local community because it is manifested in the form of taboos and even traditional ceremonies. Like the unique tradition in Lengkong Village, Bojong District, Tegal City, the people in this village have beliefs and traditions in a wedding which they usually call